Improvement of neurological disorders in postmenopausal model rats by administration of royal jelly. (1st November 2016) - Minami, A.; Matsushita, H.; Ieno, D.; Matsuda, Y.; Horii, Y.; Ishii, A.; Takahashi, T.; Kanazawa, H.; Wakatsuki, A.; Suzuki, T.
Abstract: Objective: Royal jelly (RJ) from honeybees ( Apis mellifera ) has estrogenic activity. Estrogen deficiency after menopause leads to a high risk of memory impairment and depression as well as metabolic syndrome and osteoporosis. We here investigated the effect of RJ on memory impairment and depression-like behaviors in ovariectomized (OVX) rats. Methods: OVX rats were administered with RJ for 82 days. Hippocampus-dependent spatial memory and depression-like behaviors were assessed by the Morris water maze test and the forced swimming test, respectively. The weights of body, brain and uterus and the contents of protein and myelin galactolipids including galactosylceramide and sulfatide were measured. Results: Memory impairment and depression-like behaviors in OVX rats were recovered to the levels of sham-operated rats by RJ administration. Increased body weight and decreased uterine weight in OVX rats were recovered to the levels of sham-operated rats by 17β-estradiol (E2) administration but not by RJ administration. In contrast, brain weight was slightly increased by RJ administration but not by E2 administration. The contents of protein and myelin galactolipids were higher in the brains of RJ-administered OVX rats than in the brains of E2-administered OVX rats. Conclusion: The results suggest that RJ has a beneficial effect on neurological symptoms of a menopausal disorder.